Transient three-dimensional geometrical/thermal modelling of thermal spray: normal-impinging jet and single straight deposits - Fanicchia, F.; Axinte, D.A. (Elsevier, 2018)
A new time-dependent approach to the geometrical and thermal modelling of the deposit footprint in thermal spray processes is proposed. Based upon a three-dimensional finite-difference numerical technique, the model is composed of two integrated sections: a geometrical analysis, accounting for deposit geometry analytical prediction, and a thermal analysis that computes the system temperature history. Primary process factors for the simulation, i.e. plume distribution parameters, jet heat transfer properties and temperature-dependent deposition efficiency are determined in a preliminary stage of model application. Through computation of the simulated impact surface temperature at each instant during the simulation, the deposition efficiency-mediated growth of the deposit is accurately predicted at arbitrary values of torch feed speed. The model is flexible as it only relies on an initial calibration stage performed at a specific set of process parameters to be able to predict deposition geometries at arbitrary conditions, thus avoiding the need of complex simulations and/or knowledge of single splats impact properties. Moreover, this modelling approach has the potential to be extended to several thermal spray processes at arbitrary values of process parameters (e.g. torch design, materials, etc.), opening the way for spray automation in difficult-to-spray geometries and/or repair applications. The proposed modelling framework has been validated on Combustion Flame Spray (CFS) deposition of CoNiCrAlY alloy on stainless steel substrates, yielding low errors (< 5% on average) in predicting the deposit footprint at various torch feed speeds.